Exploring the toxicology, socio-ecological impacts and biodegradation of microplastics in Africa: Potentials for resource conservation - Gloria Ifeoma Ujuagu; Onome Ejeromedoghene; Victor Enwemiwe; Chiamaka Linda Mgbechidinma; Ahmed Olalekan Omoniyi; Abiodun Oladipo; Jintu Gu (Toxicology Reports)
Achieving upcycling and circularity in the microplastic economy predominantly depends on collecting and sorting plastic waste from the source to the end-user for resource conservation. Microplastics, whether from packaging or non-packaging materials, pose a significant environmental challenge as they are often not prioritized for collection or recycling initiatives. The presence of additives impedes the quality of plastic recyclates and the persistence of microplastics as shredded resultants remain a threat to the aquatic and terrestrial ecosystem and its biodiversity. Despite the increasing global research on microplastics, the success of plastic and microplastic waste management in Africa is yet to be fully attained. Considering the improper disposal, limited recycling and upcycling intervention, lack of policy, and strict laws against plastic waste management defaulters, the ecosystems in Africa remain immensely impacted by several socio-ecological factors leading to the loss of aquatic organisms through reducing fertility and increasing stress. As a ripple consequence, the disruption of economic activities, toxic effects on animal/human health, and climate crisis are among their impact. This review therefore provides comprehensive detail of microplastic production and challenges in Africa, the toxicology concerns, socio-ecological issues associated with microplastic waste management, and insight into approaches to mitigate plastic pollution through recycling, upcycling, bioprocessing and their biodegradation with social insects and microorganisms which may form the basis for adoption by policymakers and researchers, thereby minimizing the consequences of plastic pollution in Africa.